Analisis Faktor Risiko Gangguan Otot Rangka akibat Kerja pada Pekerja Perkantoran di Instansi X Tahun 2023 - Putri, Alvina Winners; Susilowati, Indri Hapsari Hapsari (National Journal of Occupational Health and Safety, 2023)
An uncomfortable posture when doing work for a long duration can cause work-related musculoskeletal disorders. The purpose of this study was to determine the risk factors associated with the occurrence of symptoms of work-related musculoskeletal disorders in office workers at Institution X in 2023. This study used a cross-sectional design and the occupational posture assessment Rapid Office Strain Assessment (ROSA) method then to assess complaints of musculoskeletal disorders as a whole subjectively using the NBM (Nordic Body Map). The results showed that the level of risk of complaints of musculoskeletal disorders due to work at the intermediate level requires further investigation to make improvements. Assessment using the Nordic Body Map yielded a value of 91.40% of workers who experienced complaints of musculoskeletal the skeleton due to work The parts of the body that often experience complaints of musculoskeletal disorders due to work such as: upper neck, lower neck, back and waist Distribution of complaints felt by workers aged <40 years, based on female sex, based on the most years of service as many as 60 out of 65 work chairs were damaged in adjustable mode making workers feel uncomfortable when carrying out activities in their work area.